Penerapan E-Government Di Kecamatan Sungai Kunjang Kota Samarinda - Muhammad Rachmadani Tarmiji; Muhammad Jamal Amin; Erwin Resmawan (Jurnal Ilmu Pemerintahan, 2022)
The aim of this research is to analyze and describe the implementation of E-Government in Sungai Kunjang District, Samarinda City and public opinion regarding these online-based services. The research was conducted in Sungai Kunjang District, Samarinda City. The type of research using descriptive qualitative. Data collection was carried out by means of library and field research using observation, interview and documentation methods. Data were analyzed by descriptive qualitative. Based on the data, the authors collect data, condense data, present data, then draw conclusions according to the theory of interactive data analysis developed by Miles, Huberman and Saldana. The results of the study show that the implementation of e-Government in Sungai Kunjang District has been running quite well through services using the WhatsApp application and website. The requirements for file management can be accessed through the application. The efficiency resulting from the existence of this system means that residents do not waste enough time, money and energy to take care of their needs at the sub-district and sub-district offices. Furthermore, this program can also increase the active participation of the community on various issues and problems that exist in the environment. Various kinds of the latest regulations from the city government can be directly channeled effectively to support information disclosure between the government and the community.